Transformasi Komunikasi Organisasi dan Dinamika Stratifikasi Sosial Digital di SMK Ma’arif NU 1 Rawalo - suseno; Muh. Hanif (Media Manajemen Pendidikan, 2026)
This study aims to analyze the transformation of organizational communication in the digital era at SMK Ma’arif NU 1 Rawalo Banyumas, focusing on changes in communication patterns, digital social stratification, and power relations within an Islamic-based educational environment. A qualitative approach was employed through in-depth interviews, participant observation, and documentation involving the principal, senior and junior teachers, students, and parents. The findings indicate that communication digitalization through WhatsApp and online learning platforms has transformed organizational communication from a bureaucratic hierarchical model into a digital network characterized by greater speed, flexibility, interactivity, and participation, enabling real-time information exchange and strengthening two-way communication. However, this transformation also generates digital social stratification due to disparities in technological literacy and access. Senior teachers tend to experience difficulties adapting to digital technologies and often depend on younger colleagues, while students with better technological access participate more actively in communication. Parents also face challenges in using digital communication media, affecting school interactions. Furthermore, digital communication spaces have reshaped power relations into more open and negotiable forms. These findings highlight that communication digitalization influences technical, social, and cultural dimensions, emphasizing the need for inclusive, adaptive, and Islamic value-based communication strategies.